lncRNA POLR2J4 Plays a Biomarker Role in Hepatitis B Virus-Related Hepatocellular Carcinoma Through Regulating miR-214-3p - Ji, Yimei; Chen, Xiaowei; Liu, Xin; Huang, Jianyuan; Liu, Pei (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Identifying novel therapeutic targets for hepatitis B virus (HBV)-induced hepatocellular carcinoma (HCC) has become a key goal in liver cancer research. Even though long non-coding RNAs (lncRNAs) do not code proteins, they could regulate the expression of functional genes and thus mediate disease development. The aim of this study was to estimate the role of lncRNA POLR2J4 (POLR2J4) in the progression of hepatitis B virus-related hepatocellular carcinoma (HBV–HCC) to pinpoint a potential biomarker. Materials and Methods: This study included 109 patients diagnosed with HBV-positive HCC, from whom tissue samples were collected. The expression level of POLR2J4 was evaluated by qPCR. The significance of POLR2J4 in HBV–HCC development and prognosis was estimated by Chi-square, Kaplan-Meier, and Cox analysis. In vitro, POLR2J4 was regulated in HBV–HCC cells, and its effect on cell growth and metastasis was assessed by CCK8 and Transwell assay. The interaction between POLR2J4 and miR-214-3p was evaluated through the luciferase reporter and RNA immunoprecipitation assays. Results: In tumor tissues of HBV–HCC patients, there was an observed increase in the expression of POLR2J4. The increase was closely related with patients’ presence of cirrhosis and vascular invasion, higher AFP, and advanced Edmondson grade and TNM stage. An upregulation of POLR2J4 predicted a poor prognosis for HBV–HCC patients and served as an independent indicator. In HBV-related HCC cells, silencing POLR2J4 suppressed cell proliferation, migration, and invasion. Furthermore, POLR2J4 negatively regulated miR-214-3p reversing the inhibition of cellular processes. Conclusion: POLR2J4 acted as a prognostic biomarker and a tumor promoter of HBV–HCC by modulating miR-214-3p. Cite this article as: Ji Y, Chen X, Liu X, Huang J, Liu P. LncRNA POLR2J4 plays a biomarker role in hepatitis B virus-related hepatocellular carcinoma through regulating miR-214-3p. Turk J Gastroenterol. 2024;35(10):787-794.